Advanced Magnetic and Optical Materials - Tiwari, Ashutosh (Advanced Material Ser., 2016)
Advanced Magnetic and OpticalMaterials offers detailed up-to-date chapters on the functional optical and magnetic materials, engineering of quantum structures, high-tech magnets, characterization and new applications. It brings together innovative methodologies and strategies adopted in the research and development of the subject and all the contributors are established specialists in the research area. The 14 chapters are organized in two parts: Part 1: Magnetic Materials -Magnetic Heterostructures and superconducting order -Magnetic Antiresonance in nanocomposites -Magnetic bioactive glass-ceramics for bone healing and hyperthermic treatment of solid tumors -Magnetic iron oxide nanoparticles -Magnetic nanomaterial-based anticancer therapy -Theoretical study of strained carbon-based nanobelts: Structural, energetical, electronic, and magnetic properties -Room temperature molecular magnets - Modeling and applications Part 2: Optical Materials -Advances and future of white LED phosphors for solid-state lighting -Design of luminescent materials with "Turn-on/off" response for anions and cations -Recent advancements in luminescent materials and their potential applications -Strongly confined quantum dots: Emission limiting, photonic doping, and magneto-optical effects -Microstructure characterization of some quantum dots synthesized by mechanical alloying -Advances in functional luminescent materials and phosphors -Development in organic light emitting materials and their potential applications